Amino acid permeases in developing seeds of Vicia faba L.: Expression precedes storage protein synthesis and is regulated by amino acid supply - Sauer, Norbert; et al. (Plant Journal, 2001)
Full length cDNAs encoding three amino acid permeases were isolated from seed-specific libraries of Vicia faba. The predicted proteins VfAAP1, VfAAP3 and VfAAP4 share up to 66% identity among themselves. Functional characterization of VfAAP1 and VfAAP3 in a yeast mutant showed that these permeases transport a broad range of amino acids. However, VfAAP1 had a preference for cysteine and VfAAP3 for lysine and arginine. VfAAP1 was highly expressed in cotyledons at early developmental stages and moderately in other sink tissues. Its peak of expression in cotyledons corresponded to the appearance of storage protein transcripts, suggesting that this transporter fulfills an important role in providing amino acids for storage protein biosynthesis. VfAAP3 was expressed most abundantly in maternal tissues, that is in roots, stems, gynoecia, pods and seed coats at different developmental stages. VfAAP4 transcripts could not be detected by northern hybridization. In situ hybridization showed that VfAAP1 mRNA is distributed throughout cotyledon storage parenchyma cells, but could not be detected in the abaxial epidermal cell layer. It also accumulate in the chlorenchyma and thin-walled parenchyma cells of seed coats. VfAAP1 mRNA leveis were lower in cotyledons cultured in the presence of glutamine, whereas expression of a vicilin storage protein gene was up-regulated under similar conditions. Cysteine repressed the expression of the GUS reporter gene under control of the VfAAP1 promoter, suggesting that this transporter is modulated at the transcriptional level. Regulation of amino acid transport in relation to storage protein accumulation is discussed.
Keywords: Amino acid permease; Gene regulation; Legume seed development; Storage protein; Transporter